Integration of Kekehan Traditional Game to Measure Students' Creative Thinking Skills in Physics Learning - Damarsha, Adrian Bagas; Arrafi', Wadhifah Qiyyamul Lailli; Ariana, Indri Maya; Sunarti*, Titin; Suprapto, Nadi; Nisa', Khoirun (Jurnal Pendidikan Sains Indonesia, 2025)
Physics learning is expected not only to focus on understanding theory, but students can apply physics in everyday life. One example of the application of physics that can be used in accordance with the era of society is the traditional game of kekehan. Therefore, this study aims to analyze the validation of the integrated test instrument of traditional kekehan games and the response of students after administering the test instrument. This research uses research and development design with ADDIE model in its development flow. The subject of the study was a test instrument developed integrated with traditional kekehan games, and trials on students. The data analysis technique used was quantitative descriptive from the validity and reliability values. The results obtained show that the instrument developed has very valid criteria. The results of suggestions from validators for improvement are to clarify the question instruction sentence briefly and concisely. The results of students' responses show that the difficulty of the physics concept of kekehan. This shows that there is still a lack of giving problems in physics learning as contextual problems. The general results can be concluded that the integrated creative thinking skills test instrument questions using the kekehan game can be used to test students' thinking skills